Dynamic constitutive behavior investigation of a novel low alloy ultra-high strength steel. (6th January 2021) - Lu, Tie; Li, Yong; Zhao, Hongjin; Wang, Chunxu; Han, Shun
Abstract: The goal of this work is to reveal the dynamic mechanical properties and constitutive relationship of a novel low alloy ultra-high strength DT506 steel under high strain rates. The quasi-static state and dynamic compression behavior of the material at the strain rates of 10 −3 –10 3 s −1 were examined using an MTS landmark electro-hydraulic servo universal tester and a Split-Hopkinson bar (SHPB). The results show that DT506 steel is a strain-rate-sensitive material that shows an increase in strength with increasing strain rate. Based on the quasi-static and dynamic compression data, the parameters in the Cowper-Symonds (C-S) and the Johnson-Cook (J-C) models are determined. Since the previously developed models are cannot accurately predict the effect of the strain rate. A new theoretical model is obtained through the optimization of the parameters in the standard J-C model. The optimized model greatly improves the prediction accuracy of the true stress-strain dynamic behavior of materials. This new model is helpful for the verification of the underlying mechanism of the dynamic behavior of the material. Test results may provide basic data for future research on dynamic mechanical properties and constitutive relationship of metal alloys.